Public Investment and its impact on the regional PIB of Huánuco period 2010 – 2017 - Santiago Espinoza, Vladimir Hamilton (2018)
Objective. Determine the incidence of public investment in the regional GDP of Huánuco period 2010 - 2017. Method. The research was basic, with the purpose of enriching the knowledge regarding the proposed variables, being the descriptivecorrelational level with a non-experimental transectional correlational-causal type design. Secondary information was collected from the evaluation periods to determine the relationships between the two. Results. It has been possible to verify that the growth rates of this indicator are above 4%, with public management being a component equivalent to 22% annual average, with the years 2012 and 2017 with the highest incidence between both variables 25%, and 27% respectively. Regarding trends, the Regional GDP shows that it is in the process of economic expansion and consolidation in the evaluation periods, since there are no decreases in these periods. Conclusion. there is a positive incidence between public investment and the Regional GDP between the periods 2010 and 2017, evidenced by a correlation level of 0.9 according to the Pearson statistician, and the linear equation with a positive slope Y = 2.1932X + 2E + 09 where X = investment public, and Y = Regional GDP.